Assimetrias de informação, nova economia institucional e custos de transação : uma análise das convergências entre Stiglitz e Williamson - Melo, Elivânia Bezerra de (2013)
This work has a double goal: First, after defining the key elements of the Neoclassical program me of scientific research (PSR), it aims to highlight the epistemological incompatibilities between the Information Economy and this PPC neoclassical; such incompatibilities are reflected by the construction of a PSR alternative (STIGLITZ, 2000). In a second step, we will highlight the convergences between the Information Economy and New Institutional Economy (NIE), specifically the Transaction Cost Economy, in order to demonstrate and to what extent this convergence allows the development of an alternative program. We attempted to show that the relaxation of the auxiliary hypothesis that the information is perfect, although it could be made compatible with the core of the program, at least in the version of Stigler (1961), constituted a much more complex problem, being incompatible with various components hard core PSR Neoclassical. From a theoretical perspective, the existence of information asymmetries implies the instability of market equilibrium provides the conditions for the development of speculative behavior (HERSCOVICI, 2012) and thus justifies the active role of different institutions in the concrete functioning of different markets. Thus, both the Information Economy, as the New Institutional Economy, point to the limits of the price system as a regulatory mechanism of the market, and demonstrate the need for institutional variables to reduce uncertainty and "contain the inherent instability of the market game." Moreover, it may be noted that while the analysis of the Information Economy examines the market failures associated with information asymmetries, analyzing the impacts of this on the balance of the market, the NIE under the Transaction Cost Economy, examines the mechanisms by which information problems can be partially overcome, pointing to the construction of new mechanisms and instances of negotiation.